The prevalence and social determinants of fruit and vegetable consumption among adults in Kenya: A cross-sectional national population-based survey, 2015 - Supa Pengpid (2019)
© Supa Pengpid et al. Introduction: Low fruit and vegetable consumption contributes significantly to the burden of disease. The study aimed to assess the prevalence and correlates of fruit and vegetable (FAV) consumption among adults in a national survey in Kenya. Methods: A national cross-sectional study based on a stratified cluster random sampling was conducted in 2015. The total sample included 4479 individuals 18-69 years, (females = 60.0%; median age 38.0 years, Inter Quartile Range 23) from Kenya. Sociodemographics, health risk behaviour and anthropometric data were collected using the WHO-STEPS questionnaire. Results: On average, participants had 0.78 servings of fruits a day, 1.31 servings of vegetables a day, and 2.09 servings of FAV. Only 12.4% of respondents had two or more servings of fruit a day, 7.4% had three or more servings of vegetables a day and 94.0% had less than five servings of FAV a day. In adjusted logistic regression analysis, higher education (Odds Ratio=OR: 1.68, Confidence Interval = CI: 1.18, 2.39), greater wealth (OR: 1.61, CI: 1.04, 2.48), and being a Kikuyu (OR: 2.17, CI: 1.46, 3.23) or Luo (OR: 1.58, CI: 1.05, 2.37) were associated with two or more servings of fruits daily. Urban residence (OR: 0.44, CI: 0.23, 0.82) and being male (OR: 0.72, CI: 0.53, 0.98) decreased the odds, and older age (OR: 1.68, CI: 1.05, 2.69) and being Luo (OR: 2.84, CI: 1.53, 5.27) increased the odds of having three or more servings of vegetables daily. Being male (OR: 0.71, CI: 0.52, 0.99) and being Luo (OR: 0.40, CI: 0.23, 0.70) decreased the odds and urban residence (OR: 2.50, CI: 1.27, 4.96) increased the odds of inadequate (< five servings) FAV consumption. Conclusion: A high prevalence of inadequate FAV consumption was found, and risk factors identified, such as being female, lower education, urban residence, and not being Luo, that may help in guiding strategies to increase FAV consumption.